(untitled) (Journal of Surgical Sciences, 2019)
Objectives: To correlate the findings of FNAC with final histological report in parotid gland swelling and to find out the histological types of parotid neoplasm. Methods: An attempt has been made to find out age and sex distribution, FNAC findings and histological type of parotid gland neoplasm. A total 30 cases were studied from the inpatient departments of General Surgery and Otolaryngology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka since July, 2011 to April, 2013. Result: Regarding investigations in this series Fine Needle Aspiration Cytology (FNAC) was done in all 30(100%). In this series out of 30 cases of parotid neoplasm 23 (76.66%) cases were benign and rest 07 (23.33%) were malignant. Among the benign tumours commonest was pleomorphic adenoma 20 (66.66%) and regarding malignancy Mucoepidermoid Carcinoma was most common 3 (10%) then adenoid cystic carcinoma 2 (6.66%). Out of 7, 3 were stage 3(42.85%) and 3 were stage 4(42.85%). In histological grading 3 were low grade (42.85%) and 4 were high grade (57 .14%). All the patient underwent partotidectomy. Few were treated by radical parotidectomy plus radiotherapy. Early diagnosis and treatment of major salivary gland tumour is likely to lead a fare outcome. Conclusion: FNAC is a useful preoperative diagnostic tool for parotid gland swelling with high specificity and sensitivity. Though it is a small series to comment on the whole spectrum of the parotid gland swelling in Bangladesh, yet this study has been designed to see the role of FNAC in neoplastic parotid lesion which will be beneficial for proper management. Journal of Surgical Sciences (2013) Vol. 17 (1) : 30-34